Plan educativo virtual para mejorar el proceso de aprendizaje en los estudiantes con Necesidades Educativas Especiales de la Universidad Técnica de Babahoyo - Gómez Alvarado, Dalila Geoconda (2023)
Higher Education must focus on achieving inclusive goals that guarantee the same educational access opportunities for all students, while virtuality was being developed, a weakness was evidenced in the learning process of students with some type of disability. The main objective is to propose a virtual educational plan to improve the learning process in students with special educational needs at the Universidad Técnica de Babahoyo. The type of research according to its purpose is applied, with a mixed approach, descriptive - explanatory scope and non-experimental research design. The sample consisted of 62 students with special educational needs, the data collection technique was the survey and the questionnaire previously validated by experts as an instrument. The results showed that the Virtual Educational Plan and Learning Process variables have a Spearman's Rho correlation level of 0.628, which shows a positive relationship and an average relational level of 61.3%. It is concluded that there is a need to develop a virtual educational plan that is inclusive, has relevance, presents a functional and interactive virtual environment, to develop relevant characteristics in the learning process since there is evidence of weakness in fluid communication between student - teacher, in addition of an interaction of the actors without the motivating effect, added to these inflexible strategies in the learning process. The design focused on three axes: an inclusive program, a usable and accessible program, and finally an interactive program.